2014
DOI: 10.1186/1471-2164-15-1102
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the effect of Vibrio alginolyticus infection on the innate immunity-related complement pathway in Epinephelus coioides

Abstract: BackgroundOrange-spotted grouper (Epinephelus coioides) with protogynous hermaphroditic features are one of the most economically important aquaculture species in Taiwan. However, larvae stage grouper are susceptible to infection by the bacterial pathogen Vibrio alginolyticus. To better understand the molecular mechanisms of the immune response to V. alginolyticus in Epinephelus coioides larvae, we used high-throughput deep sequencing technology to study the effect of infection on gene expression.ResultsA tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 50 publications
2
18
1
Order By: Relevance
“…KF294753). mRNA was isolated and transcribed into complementary first strands (c) according to previously published methods for real-time comparative qPCR to obtain DNA and detect the relative expression levels of each gene [3,17]. The primers used in these experiments are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…KF294753). mRNA was isolated and transcribed into complementary first strands (c) according to previously published methods for real-time comparative qPCR to obtain DNA and detect the relative expression levels of each gene [3,17]. The primers used in these experiments are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Vibrio alginolyticus is an important opportunistic pathogen and causes vibriosis, one of the most prevalent diseases in maricultured animals and seafood consumers. 1 The large yellow croaker ( Pseudosciaena crocea ) is one of the most economically important maricultured fish species in southeast China. 2 V. alginolyticus readily causes vibriosis in cultured P. crocea , which results in severe economic losses in the warm-water season.…”
Section: Introductionmentioning
confidence: 99%
“…It is an opportunistic pathogen and a major cause of vibriosis in aquatic animals, resulting in severe economic losses worldwide (6,7). Recent studies suggested that V. alginolyticus is also a potential human pathogen (8).…”
mentioning
confidence: 99%